2018
DOI: 10.1029/2018gb005960
|View full text |Cite
|
Sign up to set email alerts
|

Manure and Mineral Fertilizer Effects on Crop Yield and Soil Carbon Sequestration: A Meta‐Analysis and Modeling Across China

Abstract: Manure application to soil has declined globally due to increased availability of mineral fertilizers. However, mineral fertilizer overuse has caused serious consequences for soil quality and the environment. We analyzed the results of 20 long‐term field trials (22–32 years, start year [ranged from 1980 to 1990] to 2012) and combined this with a climate change model and soil organic carbon (SOC) model to quantify the importance of manure and mineral fertilizers for grain yield and SOC sequestration across crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…Therefore, this has been omitted from the model. However, since the application of mineral N fertilizer generally leads to an increase in crop yields (Jiang et al, 2018), this effect can be included by increasing the NPP model input. Also the effect of cover crops on N 2 O emissions was not included as an independent variable in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this has been omitted from the model. However, since the application of mineral N fertilizer generally leads to an increase in crop yields (Jiang et al, 2018), this effect can be included by increasing the NPP model input. Also the effect of cover crops on N 2 O emissions was not included as an independent variable in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest SOC bene ts occurred on high SOC soil possibly due to the negative relationship between the initial SOC of soil, a primary driver (CO 19.2%, CM 24.2%, Fig. 2d-e), and SOC bene ts 40 . Thus, depending on initial SOC levels, speci c compost must be chosen to achieve synergistic bene ts as outlined below.…”
Section: Determinants Of a Precision Compost Strategymentioning
confidence: 99%
“…On the other hand, it can provide available plant nutrients and improve soil quality (Cai et al, 2019; Chen et al, 2017; Kidd et al, 2017; Luo et al, 2018), and thereby contribute to SOC accrual indirectly through increasing C input from plant biomass. Meta‐analysis studies found that long‐term manure application significantly increased the concentration (Chen et al, 2017; Du et al, 2020; Han et al, 2016; Jiang et al, 2018; Liu et al, 2020; Luo et al, 2018) and stock (Gross & Glaser, 2021; Maillard & Angers, 2014; Ren et al, 2018) of SOC in the majority of experiments, while the change magnitudes varied substantially among different experiments. So far, the responsible factors, especially their relative importance, for such variability are still not well assessed.…”
Section: Introductionmentioning
confidence: 99%